Cellulolytic fruits wastes: a potential support for enzyme assisted protein production - Olorunnisola, K.S; Jamal, Parveen; Karim, M. I.A; Alam, Md Zahangir; Muyibi, Suleyman Aremu (Asian Network for Scientific Information, 2013)
White rot fungus are valuable class of filamentous and spore forming strains capable of use as animal feed supplements when cultivated under submerged state bioconversion. Selected bacidiomycetes; Phanerochaete chrysosporium (P. chrysosporium), Panus tigrinus M609RQY (M6) and RO2 were grown solely on liquid and solid substrates of banana peel, pineapple peel and papaya peel. On banana peel (solid and liquid), RO2 has the highest protein (15.88 and 14.08mg/g), followed by P. chrysosporium (15.09 and 13.56mg/g) and M6 (13.24 and 8.07mg/g). On pineapple peel, RO2 protein is 17.71 and 12.79mg/g, M6 12.61 and 12.32mg/g. P. chrysosporium produced 12.27 and 6.85mg/g protein. RO2 produced 15.64 and 12.94mg/g protein on Papaya peel, M6 produced 9.23 and 10.09mg/g while P. chrysosporium synthesized 8.16 and 10.21mg/g. P. chrysosporium, M6 and RO2 produced good α-amylase and cellulase enzyme activities that assisted in substrate degradation for protein synthesis.